The use of particulate injection moulding for fabrication of sports and leisure equipment from titanium metals - Ewart, P. D. (Proceedings, 2018)
Advanced materials such as metal alloys, carbon fibre composites and engineered polymers have improved athlete performances in all sporting applications. Advances in manufacturing has enabled increases in design complexity and the ability to rapidly prototype bespoke products using additive manufacturing also known as 3D printing. Another recent fabrication method widely used by medical, electronics and armaments manufacturers is particulate injection moulding. This process uses exact quantities of the required material, in powder form, minimising resource and energy requirements in comparison to conventional manufacturing techniques. The process utilises injection moulding techniques and tooling methods developed and used in the plastics industry. It can produce highly complex component geometries with excellent repeatability and reduced cost where volume manufacturing is required. This is especially important when considering materials such as titanium that are not only expensive in comparison to other metals but are difficult to process by regular machining and fabrication methods. This work presents a review of titanium use in the sporting sector with a focus on sporting devices and equipment. It also proposes that the sports engineering sector could increase performance and enable improvements in safety by switching to design methods appropriate to processing via the particulate injection moulding route.